Air dalam Al-Qur’an: Panduan Hidrosentrisme untuk Mengatasi Krisis Air Bersih Global - Iwan Satiri; Damri Hasibuan; Mohamad Taufik; Ridho Wahyudi Anis Usman (Rayah Al-Islam, 2026)
The global clean water crisis is a critical environmental challenge driven by an anthropocentric paradigm that exploits nature. This study aims to examine the concept of Quran-based hydrocentrism as a solution to this crisis. The method employed is qualitative, utilizing literature review, thematic exegesis (maudhu'i), and philosophical reflection. The results demonstrate that the Quran positions water as a sacred foundation of life and ecosystems, the balance of which must be preserved. The novelty of this research lies in reconstructing the ecological paradigm from anthropocentrism toward Islamic spiritual hydrocentrism. The policy implication provides a strong theological basis for formulating global water conservation regulations and religious community-based environmental movements.